(untitled) (International Journal of Nursing Care, 2020)
The increased incidence of pressure ulcers among inpatient patients has been reported in JDWNRH. As a result, there was an increase in the length of hospitalization, over utilization of resources and affects patient’s satisfaction. There was also a lack of adequate evidence on knowledge, attitude and practice for effective prevention of pressure ulcers. The study was conducted to study the knowledge, attitude, and practice of pressure ulcers among nurses of JDWNRH. Cross-sectional was used among 389 nurses working in all inpatients department. The results found that the knowledge on pressure sore was good (64%) but the attitude (75.1%) and Practice (93.1%) to prevent pressure ulcer was low. Scientific analysis also showed that knowledge had a significant correlation with working experience (p=0.034), which reveals that the longer the duration in the service, the more the knowledge was gained. Subsequently, the more the knowledge was gained, the practice on prevention on pressure ulcer increases (p=0.036). The study found out that retention of the experienced nurses is extremely important because CME updates the knowledge, which eventually improves the patient’s care whereas behaviour change remains challenging because of individual attitude and perception.